Wiskott-Aldrich syndrome protein forms nuclear condensates and regulates alternative splicing - Yuan, Baolei; Zhou, Xuan; Suzuki, Keiichiro; Ramos-Mandujano, Gerardo; Wang, Mengge; Tehseen, Muhammad; Cortés-Medina, Lorena V.; Moresco, James J.; Dunn, Sarah; Hernandez-Benitez, Reyna; Hishida, Tomoaki; Kim, Na Young; et al. (Nature Communications, 2022)
The diverse functions of WASP, the deficiency of which causes Wiskott-Aldrich syndrome (WAS), remain poorly defined. We generated three isogenic WAS models using patient induced pluripotent stem cells and genome editing. These models recapitulated WAS phenotypes and revealed that WASP deficiency causes an upregulation of numerous RNA splicing factors and widespread altered splicing. Loss of WASP binding to splicing factor gene promoters frequently leads to aberrant epigenetic activation. WASP interacts with dozens of nuclear speckle constituents and constrains SRSF2 mobility. Using an optogenetic system, we showed that WASP forms phase-separated condensates that encompasses SRSF2, nascent RNA and active Pol II. The role of WASP in gene body condensates is corroborated by ChIPseq and RIPseq. Together our data reveal that WASP is a nexus regulator of RNA splicing that controls the transcription of splicing factors epigenetically and the dynamics of the splicing machinery through liquid-liquid phase separation. Wiskott-Aldrich syndrome is caused by mutations in WASP, but the underlying mechanisms remain to be explored. Here the authors reveal that WASP deficiency results in aberrant RNA splicing, and that WASP regulates the transcription of splicing factor genes and co-transcriptional RNA splicing via a phase-separation process that involves splicing factors and nascent RNA.